2012
DOI: 10.15580/gjss.2012.2.gjmbs1225
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Research Productivity in the Virtual Worlds Literature: A Bibliometric Approach

Abstract: Since the beginning of the 21st century, the internet has provided a much more dynamic platform, becoming more visual and allowing users to interact with each other in communities and share information in real time. The new Internet is a social media, and online communities are taking on a new dimension, quite literally, in the form of immersive 3D virtual worlds, such as such as Active Worlds, OSGrid, and Second Life. Surprisingly, 80% of active internet users have a registered account in virtual worlds which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, often, as in this case, an established law can remain debatable among scholars. Many well-known authors, including Baby and Kumaravel (2012), Burrell (2008), Egghe (2010), Fang and Fang (1995), Huber (2002), Naranan (1971), Potter (1981), Pao (1985), Schorr (1974), Sudhier (2013), Suen and Yang (2012), Torbati and Chakoli (2013) and Vlachy (1976), have subjected the pioneer study of Lotka to testing. Studies on the fitness of Lotka's Law began in a systematic manner starting with Vlachy (1978), who observed that non-conformity of Lotka's assertions could be influenced by the variables discussed earlier.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, often, as in this case, an established law can remain debatable among scholars. Many well-known authors, including Baby and Kumaravel (2012), Burrell (2008), Egghe (2010), Fang and Fang (1995), Huber (2002), Naranan (1971), Potter (1981), Pao (1985), Schorr (1974), Sudhier (2013), Suen and Yang (2012), Torbati and Chakoli (2013) and Vlachy (1976), have subjected the pioneer study of Lotka to testing. Studies on the fitness of Lotka's Law began in a systematic manner starting with Vlachy (1978), who observed that non-conformity of Lotka's assertions could be influenced by the variables discussed earlier.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lotka's Law has been modified by Baby and Kumaravel (2012), Burrell (2008), Coile (1977), Egghe (2010), Fang and Fang (1995), Huber (2002), Naranan (1971), Pao (1985), Potter (1981), Schorr (1974), Sudhier (2013), Suen and Yang (2012) and Vlachy (1976). Recently, Torbati and Chakoli (2013) suggested that the modifications and non-conformity to Lotka's assertions were a result of the counting method adopted, period covered, sources of data, community of authors, nature of discipline, errors in data and statistical test adopted.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantity apportioned to publication of articles in a particular field varies in context, subject and phenomenon. Several studies by Araújo, Moreira, Furtado, Pequeno, and Andrade (2014), Baby and Kumaravel (2012), Egghe (2010), Naranan (1971), Ruiz-Castillo and Costas (2014), Schorr (1974), Sudhier (2013), Suen and Yang (2012) and Torbati and Chakoli (2013) gave widespread explanations over the disparity of research output patterns and visibility of authors' research work. A follow-up research by Onyancha (2010), indicates that publication counts and analysis are progressively flattering to the global setting such that, in-depth meter of research output is counted through bibliometric analysis.…”
Section: Literature Reviewmentioning
confidence: 99%